Β-Adrenergic blockade combined with subcutaneous B-type natriuretic peptide: a promising approach to reduce ventricular arrhythmia in heart failure?. Issue 11 (25th March 2014) - Thireau, Jérôme; Karam, Sarah; Roberge, Stéphanie; Roussel, Julien; Aimond, Franck; Cassan, Cécile; Gac, Arnaud; Babuty, Dominique; Le Guennec, Jean-Yves; Lacampagne, Alain; Fauconnier, Jérémy; Richard, Sylvain
Abstract : Aims: Clinical studies failed to prove convincingly efficiency of intravenous infusion of neseritide during heart failure and evidence suggested a pro-adrenergic action of B-type natriuretic peptide (BNP). However, subcutaneous BNP therapy was recently proposed in heart failure, thus raising new perspectives over what was considered as a promising treatment. We tested the efficiency of a combination of oral β1-adrenergic receptor blocker metoprolol and subcutaneous BNP infusion in decompensated heart failure. Methods and results: The effects of metoprolol or/and BNP were studied on cardiac remodelling, excitation–contraction coupling and arrhythmias in an experimental mouse model of ischaemic heart failure following postmyocardial infarction. We determined the cellular and molecular mechanisms involved in anti-remodelling and antiarrhythmic actions. As major findings, the combination was more effective than metoprolol alone in reversing cardiac remodelling and preventing ventricular arrhythmia. The association of the two molecules improved cardiac function, reduced hypertrophy and fibrosis, and corrected the heart rate, sympatho-vagal balance (low frequencies/high frequencies) and ECG parameters (P to R wave interval (PR), QRS duration, QTc intervals). It also improved altered Ca 2+ cycling by normalising Ca 2+ -handling protein levels (S100A1, SERCA2a, RyR2), and prevented pro-arrhythmogenic Ca 2+ waves derived from abnormal Ca 2+ sparks in ventricular cardiomyocytes. Altogether these effects accounted for decreased occurrence of ventricular arrhythmias. Conclusions: Association of subcutaneous BNP and oral metoprolol appeared to be more effective than metoprolol alone. Breaking the deleterious loop linking BNP and sympathetic overdrive in heart failure could unmask the efficiency of BNP against deleterious damages in heart failure and bring a new potential approach against lethal arrhythmia during heart failure.